Can Rational-Emotive Behavior Therapy (REBT) Reduce Academic Anxiety in High School Students? - Debby Nia Novinta; Endah Mastuti (Psikostudia : Jurnal Psikologi, 2023)
Teenagers experience rapid development and growth during high school. During this phase, adolescents experience many challenging changes, including changes in emotional and physical development. If these changes are not properly managed, they can lead to problems such as anxiety. One of the sources of teenage anxiety is their academic problems. "Academic anxiety" is what this form of anxiety is called. It can be a challenge for students to focus, learn, and feel confident. Interventions are needed to assist students in controlling their anxiety so that they can be successful in achieving their academic endeavours. The purpose of this study was to assess the effectiveness of the Rational Emotive Behavior Therapy (REBT) method in reducing high school students' academic anxiety levels. The participants in this study were 17-year-old high school students. The method used is a single case experimental design in which this single case refers to one individual within a certain scope. The results showed that REBT can reduce high school students' academic anxiety levels. Based on their experience of carrying out activities during the intervention, students are aware of irrasional thoughts that lead to behavior and feelings and replace them with rational thoughts by confronting these irrasional thoughts.Remaja mengalami perkembangan dan pertumbuhan yang pesat selama masa sekolah menengah atas. Pada fase ini remaja mengalami banyak perubahan yang menantang, termasuk perubahan perkembangan emosi dan fisik. Jika perubahan ini tidak dikelola dengan benar, maka dapat menimbulkan masalah seperti kecemasan. Sumber kecemasan remaja salah satunya ialah persoalan akademik mereka. "Kecemasan akademis" adalah sebutan yang diberikan untuk bentuk kecemasan ini. Hal ini dapat menjadi tantangan bagi siswa untuk fokus, belajar, dan merasa percaya diri. Intervensi diperlukan untuk membantu siswa dalam mengendalikan kecemasan mereka sehingga mereka dapat berhasil dalam mencapai usaha akademis. Tujuan dari penelitian ini adalah untuk menilai efektivitas Rational Emotive Behaviour Therapy (REBT) dalam menurunkan tingkat kecemasan akademis siswa sekolah menengah atas. Partisipan penelitian ini adalah siswa sekolah menengah atas yang berusia 17 tahun. Metode yang digunakan adalah single case experimental design yang dimana single case ini mengacu pada salah satu individu didalam suatu lingkup tertentu. Hasil penelitian menunjukkan bahwa REBT dapat menurunkan tingkat kecemasan akademis siswa SMA. Berdasarkan pengalaman mereka melakukan aktivitas selama intervensi, siswa menyadari pemikiran irasional yang mengarah pada perilaku dan perasaan dan menggantinya dengan pemikiran rasional dengan cara mengkonfrontasi pemikiran yang irasional tersebut.